A Nonexplosive Method for Simulating Stress Waves of Large-Scale Underground Explosions. (31st July 2022) - Ji, Yuguo; Pan, Yuefeng; Deng, Shuxin; Gao, Fei; Zhao, Zhangyong; Xu, Tianhan; Yue, Songlin; Li, Zhihao
Abstract : In the large-scale underground explosion, the dynamic mechanical behavior of deep rock mass under the coupled loading of the high in situ stress and the explosive stress wave is difficult to study. And the coupled loading of the in situ stress and the stress waves of large-scale underground explosions are hard to simulate. Based on this problem, an experimental device was developed, and a nonexplosive method for simulating stress waves of large-scale underground explosions was presented by us. In the experimental device, the impact energy is provided by the high-pressure gas in the air chamber, the stress wave is generated by the impact of the piston, and the waveform of the stress wave is adjusted by the composite pulse shaper. The adjusted stress wave can be transmitted to the container, where the coupled loading of the stress wave and the confining stress can be realized. The stress wave that corresponded to the real explosion is obtained by the developed device, and the function of the composite pulse shaper for adjusting the waveform is verified in the experiments by using a variety of mediums for wave adjustment. The experimental and calculation results showed that the stress wave corresponding to underground explosion at kilotons of equivalent on rock mass at great depth can be simulated by the experimental device, and the simulated explosion equivalent and buried depth can be adjusted by controlling the experimental conditions.